Evaluación de los niveles de ruido urbano causantes de la contaminación acústica de la población urbana céntrica de la ciudad de Quinsaloma, provincia de Los Ríos 2013 - Álvarez Aguilar, Yuliana Cristina. (2014)
Evaluation to determine the incidence of urban noise levels and determining the degree of damage to the urban population of the City of Quinsaloma province of Los Ríos 2013. The research was conducted in the month of October 2013 for 15 days starting on Sunday 20 to Sunday November 3, 2013, data were taken three times a day in 10 points during peak hours in the morning from 8:00 10:00 to noon and 12:00 to 14:00 in the afternoon from 16:00 to 18:00 for a time of 10 min at each set point as established the Unified Text of Secondary Environmental Legislation Ministry of Environment ( 1999) in Book 6 Annex 5 of the permissible limits of ambient noise levels (65 dB at 20H00 06H00), mobile sources and vibration. During measurement 15 days held in the downtown area of the city of Quinsaloma, registered in the ten points values ranged maximum permissible limits laid down TULSMA from 64.66 to 72.70 dBA. The results found in 68.41 and the 10 dBA limit points above this value so this represents the sampled points as recommended by WHO exceed 45 dBA, where the population of the City of Quinsaloma recognize that because of the noise suffer sleep loss , hearing loss and loss of mental focus. Also, recognize that in the afternoon is the schedule that there is noise pollution, also corroborated that the type of business that generates more noise pollution are posts cds and vendors that generate more noise transport are motorcycles. For City Quinsaloma the main source of noise is the fleet, so it is proposed to require owners and drivers of motorcycles and the use of exhaust mufflers for the high level of noise they generate and with the help of the ministry of environment 's surveillance of the Interior Ministry, reduce the pollution source, campaigns be undertaken to improve the use of the horn. Normative regulation also at the municipal level, to establish permissible limits of noise, to have acceptable levels of permissible and noise on human health, and implement strategies in the shortest time possible.